Resistance and virulence factors of the Staphylococcus aureus - A brief review - Sued-Karam, Bruna Ribeiro; Olivella, Julianna Giordano Botelho; Cabral-Oliveira, Guilherme Goulart; Pereira-Ribeiro, Paula Marcele Afonso (Seven Editora, 2024)
Introduction: Staphylococcus aureus is an opportunistic pathogen responsible for a wide range of infections in humans and able to rapidly adapt to anti-staphylococcal antibiotics and become resistant to several classes of antibiotics (multidrug-resistant). The biofilm- producing S. aureus has become notorious for causing several infections and chronic infections due to its ability to resist therapeutic treatment by forming biofilms on abiotic and biotic surfaces. This brief literature review discusses aspects of the antimicrobial resistance and virulence factors of the S. aureus. Methods: Literature searches were performed using PubMed indexed articles published between 2010 and 2023 to identify studies relevant to the review. Results: The success of MRSA is a consequence of the most virulence factors produced by S. aureus combined with β-lactam resistance and resistance to other antibiotic classes. S. aureus attachment to medical implants and host tissue, and the establishment of a mature biofilm, play an important role in the persistence of chronic infections. S. aureus has shown an increasing number of toxins and other virulence determinants produced by them, correlating with serious diseases. Conclusion: Antibiotic resistance and biofilm-forming capacity contribute to the success of S. aureus as a human pathogen in both healthcare and community settings. DOI:https://doi.org/10.56238/sevened2024.013-005